ANALYSIS OF HOUSEHOLD DEMAND FOR COB FISH IN SANGKUMPAL BONANG MARKET, PADANGSIDIMPUAN CITY, NORTH SUMATERA PROVINCE - Hana Lubis; Trisla Warningsih; Lamun Bathara (Berkala Perikanan Terubuk, 2021)
This research was conducted on March 6 – April 23, 2020 at the Sangkumpal Bonang Market, Padangsidimpuan City, North Sumatra Province. This study aims to determine the number of cobs perchased by household consumers (kg/month) and to analyze the factors that influence the demand for cobs in Sangkumpal Bonang Market, Padangsidimpuan City. The method used is a survey metheod. The technique of determining respondents using purposive sampling with a number of respondents 60 people. The results showed that the total tuna fish purchased by household consumers was 8 kg or with a percentage of 42% as many as 28 respondents, so that the average tuna consumption in 1-30 days was 0.3 kg and the factors that influence for tuna are the variable tuna price, the variable number of family members and income, while the variables that do not affect the tuna demand are the chicken substitution price in the Sangkumpal Bonang Market, Padangsidimpuan City.